2022
DOI: 10.1111/tpj.15737
|View full text |Cite
|
Sign up to set email alerts
|

Translational repression of FZP mediated by CU‐rich element/OsPTB interactions modulates panicle development in rice

Abstract: SUMMARY Panicle development is an important determinant of the grain number in rice. A thorough characterization of the molecular mechanism underlying panicle development will lead to improved breeding of high‐yielding rice varieties. Frizzy Panicle (FZP), a critical gene for panicle development, is regulated by OsBZR1 and OsARFs at the transcriptional stage. However, the translational modulation of FZP has not been reported. We reveal that the CU‐rich elements (CUREs) in the 3′ UTR of the FZP mRNA are crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…An InDel of 9 bp in OgFZP results in the insertion of three histidine amino acids outside the single AP2 domain in the OgFZP protein. Several recent studies have shown that variations in the promoter region and 3' UTR (Untranslated Transcribed Region) of the OsFZP gene affect panicle architecture by through changes in the number of branches produced (Bai et al, 2016(Bai et al, , 2017Huang et al, 2018;Wang et al, 2020;Chen et al, 2022). Here, we observed several SNPs and InDels between the promoter of the two orthologs, which result in a differential presence of TFBSs (Fig.…”
Section: Q_7 Genetic Variations Between Os_caiapó and Og_mg12supporting
confidence: 50%
See 3 more Smart Citations
“…An InDel of 9 bp in OgFZP results in the insertion of three histidine amino acids outside the single AP2 domain in the OgFZP protein. Several recent studies have shown that variations in the promoter region and 3' UTR (Untranslated Transcribed Region) of the OsFZP gene affect panicle architecture by through changes in the number of branches produced (Bai et al, 2016(Bai et al, , 2017Huang et al, 2018;Wang et al, 2020;Chen et al, 2022). Here, we observed several SNPs and InDels between the promoter of the two orthologs, which result in a differential presence of TFBSs (Fig.…”
Section: Q_7 Genetic Variations Between Os_caiapó and Og_mg12supporting
confidence: 50%
“…5C). Recently, it has been shown that CU-rich elements (CUREs) present in the 3' UTR of the OsFZP mRNA are crucial for efficient OsFZP translational repression (Chen et al, 2022).…”
Section: Q_7 Genetic Variations Between Os_caiapó and Og_mg12mentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced expression of OsFZP at the reproductive stage increases the extent of higher order branching of the panicle, resulting in increased grain number (Bai et al, 2016). Moreover, recent studies revealed OsFZP as the causal gene of QTLs for grain number per panicle (Bai et (Bai et al, 2017;Huang et al, 2018;Chen et al, 2022). Some SNPs and InDel variations between the Os_Caiapó and Og_MG12 genomes were detected within the promoter region of the two FZP orthologs.…”
Section: Impact Of O Glaberrima Introgressions On Panicle Traits In T...mentioning
confidence: 98%